Horizontal gene transfer and recombination in Streptococcus dysgalactiae subsp. equisimilis - McNeilly, Celia L.; McMillan, David J. (Frontiers in Microbiology, 2014)
Streptococcus dysgalactiae subsp equisimilis (SDSE) is a human pathogen that colonizes the skin or throat, and cause a range of diseases, from relatively benign pharyngitis to potentially fatal invasive diseases. While not as virulent as the close relative Streptococcus pyogenes, the two share a number of virulence factors and are known to coexist in a human host. Both pre- and post-genomic studies have revealed that horizontal gene transfer and recombination occurs between these two organisms and plays a major role in shaping the population structure of SDSE. This review summarizes our current knowledge of horizontal gene transfer and recombination in the evolution of SDSE.